Invasive Species Curriculum - Charles Jacoby; Nanette Holland; Debbi Berger (EDIS)
Management agencies agree that success in dealing with invasive species relies on education and outreach. This 156-page Invasive Species Curriculum helps fill this need by providing important information about invasive species through a dozen classroom activities, glossary, list of web sites and supporting materials designed for middle school use. Each activity addresses specific Sunshine State Standards and Florida Comprehensive Assessment Test (FCAT) benchmarks for grades 6-8. Individual activities are available as separate documents through the links provided with their descriptions. Reprinted by permission of the Tampa Bay Estuary Program and the Florida Aquarium, by the UF Department of Fisheries and Aquatic Sciences, January 2007.